Caractéristiques Morphopédologiques et Géochimiques des Sols Brunifiés de Anikro et de Kahankro (Centre-Sud de la Côte d’Ivoire) - Yoboué Kouadio Emile; Kouadio Koffi Patrice; Blé Louan Odile; Yao-Kouamé Albert (European Scientific Journal, ESJ, 2018)
In an ecosystem where ferrallitization is the dominant pedogenetic process, brown soils of a particular character are observed. They are dominant clay texture, very often spotted, and heavily loaded in coarse elements consisting of ferromanganic nodules and concretions. This paper focuses on highlighting the morphopedological and geochemical characteristics, determining the originality of the brown soils observed at Anikro and Kahankro, in the region of Toumodi, in Côte d’Ivoire. In the field, the toposquencial approach has been adopted. Soil pits have been opened and described. The samples taken were then analyzed by the triacid method in view of the determination of the content of total elements horizon by horizon. The results obtained show that the brown soils observed at Anikro and Kahankro are generally regosols and cambisols. They are subject to phenomena of reworking and rejuvenation and were affected by a phenomenon of hydromorphy at the bottom of the slope. The oxidation-reduction spots that occur in soil profiles and which predispose them to concretion are more abundant in topographic top and bottom position. Chemical analysis shows that at Anikro, the silica content decreases as the depth increases. Also, iron (Fe2O3) and aluminum (Al2O3) have an antagonistic character on the midslope. While at the bottom of slope, the MgO, MnO, Al2O3 and Fe2O3 contents increase in the BfeC depth horizon, with respective values of 3.6%, 2% and 20% for each of the last two. In Kahankro soils, the antagonism exists between silica and iron. Magnesium and manganese accumulate only in the surface horizons. At the lower slopes, the highest levels of iron (30%), aluminum (20%), magnesium (1.2%) and manganese (0.4%) in the Bg horizons begin with horizon A3. These high grades are obtained due to pseudogleyic to gleyic characters of soils located at this topographic position. The various oxides measured sometimes show a dispersed character according to the locality in relation to the nature of the rock formations whose alteration has been given to the soil. The various characteristics of the soils described reveal their particular characteristics. These soils deserve to be referred to as browned soils.